The map of payments in Hungary - István Helmeczi (Magyar Nemzeti Bank, 2011)
Until recently only aggregate data were available on national payment turnover. In reality, however, there are substantial differences across individual settlements (or between the various districts of Budapest). As a result, there is hardly any settlement which would be more or less on a par with the 'national average' in terms of the volume of payments. This paper presents Hungary's payments infrastructure (its supply of bank branches, automated teller machines and merchant PoS terminals) and payment transactions between individual counties and settlements - which, in principle, reflect well their economic relationships - plotted on maps and summarised in table form. In addition, data on individual settlements are made available for researchers and those with interest in the subject.
Keywords: H30; J10; R10; R50; Y10; 330; payments; map; bank branch; bank card; POS; ATM; transfer; batch credit transfer; direct debit; statistics; county; settlement; Zahlungsverkehr; Bankgeschäft; Räumliche Verteilung; Ungarn